Autonomous car using full mapping GPS system - Sakkhor, Tanveer Hossen; Zaman, Samin Saksiat; Al Sadi, Md. Arafat; Mahmud, Abdullah Al Nayeem (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.